Wakakosha “You are Worth it”: reported impact of a community-based, peer-led HIV self-stigma intervention to improve self-worth and wellbeing among young people living with HIV in Zimbabwe - Ferris France, Nadine; Byrne, Elaine; Nyamwanza, Owen; Munatsi, Vongai; Willis, Nicola; Conroy, Ronan; Vumbunu, Sylivia; Chinembiri, Moud; Maedziso, Samantha; Katsande, Munyaradzi A.; Dongo, Takudzwa A.; Crehan, Eimear; et al. (Frontiers in Public Health, 2023)
Self-stigma -negative self-judgements or core beliefs -can result in feelings of shame, worthlessness and self-blame, and impacts social interaction, mental health and health service utilization among people living with HIV (PLHIV). Few interventions target self-stigma among PLHIV and, to our knowledge, none until now for adolescents and young people LHIV (AYPLHIV) in sub-Saharan Africa. We present qualitative findings on the perceived impact of a self-stigma intervention (Wakakosha, 'You are worth it').The Wakakosha intervention adopted Inquiry-Based Stress Reduction (IBSR) at its core -a unique way of identifying and questioning deeply rooted self-stigma, combined with mindfulness, meditation and creativity. The intervention consisted of 16x3 hour group sessions. Supporting the intervention was a 156-page activity journal. We utilized a qualitative enquiry to explore the perceived impact of the intervention at various time points between November 2021 and November 2022, with 62 participants (n=32 female). Discussions explored experiences of being involved in the intervention and any reports on changes in relation to self-stigma and shame. Additionally, we reviewed intervention documentation and creative elements. A thematic analysis guided generation of themes across all data sources.Both intervention participants and Coaches described the transformative effect of the intervention, detailing their experiences before and after. Main themes that emerged were positive changes around: self-confidence, self-agency, sense of purpose/meaning, body positivity, improved communication and personal/family relationships and, forgiveness. The intervention also transferred a set of practical skills on self-inquiry, mindfulness, meditation and creativity that continued to be used in participants' daily lives.The Wakakosha intervention, using IBSR supported by music, creativity, writing and mindfulness techniques, showed potential for reducing self-stigma and improving self-worth among AYPLHIV. It also transferred practical skills to intervention participants and peer Coaches, building their capacity to support others and deal with life challenges beyond HIV. The next phase is to continue supporting the young people to ensure fidelity as the peer Coaches deliver the intervention to others. Study results indicate that culturally and practically, interventions to reduce self-stigma and/or improve self-worth operate at various levels and need to be designed and assessed at each level.